Development, validation and application of clinical simulation scenarios for assessment of stomatherapy specialists - Angélica Olivetto de Almeida; Sônia Regina Pérez Evangelista Dantas; Maria Angela Boccara de Paula; Juliany Lino Gomes Silva; Ednalda Maria Franck; Ana Railka de Souza Oliveira-Kumakura (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to build and validate three clinical simulation scenarios and report the application with candidates for the specialist's degree in stomatherapy. Methods: methodological study, building three scenarios and evaluation checklists; content validation with judges, using content validity index and Modified Kappa Coefficient; pre-test and application. Results: scenarios built based on nursing care for: 1. insufficiency and venous ulcer; 2. demarcation of intestinal stomia; and 3. Clean intermittent catheterization. In the content validation of the 24 items appreciated, 83%, 80%, and 92% were validated without change. In the pre-test, the objectives and checklists were adjusted. In the application, to standardize the evaluation, actors and evaluators were trained previously, and each candidate passed the three stations. Conclusions: scenarios built and with validated content, based on evidence and covering the three areas of stomatherapy. The pre-test allowed for adjustments in the scenarios, and the candidates achieved the expected objectives.